A combination of MTAP and BAP1 immunohistochemistry is effective for distinguishing sarcomatoid mesothelioma from fibrous pleuritis. (November 2018) - Kinoshita, Yoshiaki; Hamasaki, Makoto; Yoshimura, Masayo; Matsumoto, Shinji; Sato, Ayuko; Tsujimura, Tohru; Ueda, Hitoshi; Makihata, Satoshi; Kato, Fumiaki; Iwasaki, Akinori; Nabeshima, Kazuki
Highlights: Investigation of MTAP IHC as a good alternative assay to 9p21 FISH for diagnostics. MTAP IHC discriminates sarcomatoid mesothelioma from fibrous pleuritis. A combination of MTAP IHC and BAP1 IHC increases the sensitivity for MPM diagnosis. Abstract: Objectives: Histologic diagnosis of malignant pleural mesothelioma (MPM) is not always straightforward. Loss of BRCA1-associated protein 1 (BAP1) expression as detected by immunohistochemistry (IHC) (BAP1 IHC) and homozygous deletion (HD) of 9p21 as detected by fluorescence in situ hybridization (FISH) (9p21 FISH) are effective for distinguishing malignant mesothelial proliferation from benign proliferation. We have previously reported that immunohistochemical expression of the protein product of the methylthioadenosine phosphorylase ( MTAP ) gene, which is localized in the 9p21 chromosomal region, is correlated with the deletion status of 9p21 FISH in MPM tissues. In this study, we investigated whether a combination of MTAP and BAP1 IHC could distinguish sarcomatoid MPM from fibrous pleuritis. Materials and Methods: We examined IHC expressions of MTAP and BAP1 and 9p21 FISH in sarcomatoid/desmoplastic (n = 18) and biphasic MPM (n = 12) and in fibrous pleuritis (n = 17). In biphasic MPM, only sarcomatoid components were evaluated for IHC and FISH. The sensitivity and specificity of each detection assay for discriminating MPM cases from fibrous pleuritis was determined. In addition, we compared the IHC expression of MTAP with the deletion status of 9p21 FISH. Results: MTAP IHC and BAP1 IHC showed 80% and 36.7% sensitivity, respectively, and both showed 100% specificity in differentiating MPM from fibrous pleuritis. A combination of MTAP and BAP1 IHC yielded greater sensitivity (90%) than that detected for MTAP IHC alone or BAP1 IHC alone. Moreover, a high degree of concordance was observed between the results of MTAP IHC and HD of 9p21 FISH (κ = 0.63). Conclusions: With an accurate interpretation of results, combined MTAP and BAP1 IHC is a reliable and effective method for distinguishing sarcomatoid MPM from fibrous pleuritis.